(untitled) (Journal of Partial Differential Equations, 2021)
"We investigate the p-Laplace heat equation u_t- Delta_p u=03b6(t)f(u) in a bounded smooth domain. Using differential-inequality arguments, we prove blow-up results under suitable conditions on 03b6, f, and the initial datum u_0. We also give an upper bound for the blow-up time in each case."